(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the frequency and in-hospital complications of atrial fibrillation in patients with acute ST segment Elevation myocardial infarction (STEMI). Study Design: Observational / descriptive study. Place and Duration of Study: This study was conducted at the Coronary Care Unit (CCU), Saidu Teaching Hospital, Saidu Sharif Swat from October 2015 to September 2016. Materials and Methods: This was a hospital based study in which 536 male and female patients were included, who were admitted with acute ST segment elevation myocardial infarction. These patients were observed for the development of atrial fibrillation. Those patients in whom AF was documented were further observed for complications in the form of VT, VF, stroke and death during hospital stay. Results: There were 298 (55.59%) male and 238 (44.40%) female patients. Mean age of the study population was 60.5+9.8 years. 49 (9.14%) patients developed AF. 20 (40.81%) were male, and 29 (59.18%) were female. Out of 49 patients with AF ventricular fibrillation developed in 18.36%, VT was found in 14.28% patients, 12.25% had a stroke, and the mortality rate was 14.28%. Conclusion: Atrial Fibrillation is quite common complication of acute MI in our population, and carries higher rates of in-hospital complications and death. So these patients need to be identified and treated in time.